Practical training report at Information Technology Unit Cosmopoint Sdn Bhd No 77 & 78 Jalan Mawar 1, Taman Pekan Baru, 08000 Sungai Petani, Kedah Darul Aman / Nor Shazwani Ismail - Ismail, Nor Shazwani (Universiti Teknologi MARA, Kedah, 2011)
The title of this project is "Library Management System". The main purpose of Library Management System is to store information of all books and record of borrower efficiently. It has user friendly menu driven environment to ease the use of the system. It enables productive and effective library member registration. The system able to create data, delete data and make book loan transaction which will set the date borrowed and date returned. It can also generate printed report on borrower. The project is developed in the final semester of my Diploma Computer Science program. I divided this semester into two where the first half session of the semester would be used to do the interim report such as initiation, planning and the prototype of the system. During this session, I also defined the objectives of my project, goals, scopes and problem statements so that I can complete the project easily referring to it. Gantt chart and milestones were also specified to guide my schedule to keep track of time I used in developing the system. Besides, I also have done some researches on the Cosmopoint International College of Technology Sungai Petani. I have conducted a visit to Cosmopoint International College of Technology Sungai Petani for the background studies about their library management. The management of library management is manual book loan. On the second half of my semester, I have to complete the final report, implement and test on the system. I do some reviews on the library management and then make system to enhance the college. After completing the system, test was conducted to ensure no errors and bugs occurred. The system limitation is also defined for maintenance and further enhancement in future. At the end of semester, the project was successfully developed. Though I faced problems during the development of project, but I able to find solution and finished the project before due date and as planned in the Gantt chart.